Fully Relaxed, Crack-Free AlGaN with upto 50% Al Composition Grown on Porous GaN Pseudo-Substrate - Nirupam Hatui; Henry Collins; Emmanuel Kayede; Shubhra S. Pasayat; Weiyi Li; Stacia Keller; Umesh K. Mishra (Crystals, 2022)
Fully relaxed, crack free, smooth AlxGa1−xN layers with up to 50% Al composition were demonstrated on pseudo-substrates composed of dense arrays of 10 × 10 µm2 compliant porous GaN-on-porous-GaN tiles. The AlGaN layers were grown in steps for a total of 1.3 µm. The growth conditions necessary to demonstrate high quality films at higher Al compositions also suppressed any sidewall growth.